National standards in local setting. Implementing electronic nursing and care messages at the University Hospital of North Norway - Wangensteen, Gro (Universitetet i Tromsø, 2013)
This thesis is an interpretive study examining national electronic Nursing and Care Messages (NUC messages) implemented into a local setting. From the outset the messages were created to support and enhance efficiency and quality for cross level communication when exchanging health information related to shared care. The study focuses on theory of standards and standardization as the NUC messages is to be perceived as a standard. Analytic tools from Actor Network Theory are used to examine the process of how the messages were created. This contributes to an in-depth understanding of the end-users experiences after implementation of NUC messages at the local setting, which is the University Hospital of North Norway. Findings are that even though the electronic messages enables a time efficient way of communication, the message standard still have features that negatively impacts the use of them. The NUC messages seem to have a weak inscription that makes the standard flexible and enables alternative use. Additionally, this flexibility implies that compliance to the standard is challenged. Despite various efforts from local actors in the national test and piloting phase, alternative and local translations of the standard have not been possible to negotiate after the messages were designed. The standard of NUC messages seem to have reached the state of irreversibility instantly when designed. The study examines how the standard of NUC messages regarding their naming, in-messages structures and messages pathway creates a tension when adopted into local practice with alternative requirements of communication in cross level care.